Report from the Open Problems Session at OPSFA13 - Cohl, H.S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
These are the open problems presented at the 13th International Symposium on Orthogonal Polynomials, Special Functions and Applications (OPSFA13), Gaithersburg, Maryland, on June 4, 2015.